Effect of extraction method on the chemical profiles and bioactivities of soybean hull polysaccharides. Issue 11 (9th September 2021) - Han, Lin; Song, Hong; Fu, Licheng; Li, Jun; Yang, Lina; Liu, He
Abstract: The yields, properties, and bioactivities of polysaccharides extracted by three methods from soybean hulls (SSCPs) were evaluated: hot water extraction (H‐SSCP), microwave‐assisted ammonium oxalate extraction (A‐SSCP), and microwave‐assisted sodium citrate extraction (S‐SSCP). A‐SSCP gave the highest yield of polysaccharides (9.3 ± 0.5%) although all three products had similar physicochemical characteristics and FT‐IR spectra. A‐SSCP and S‐SSCP produced polysaccharides with lower molecular weight distributions and higher total reducing power and scavenging ability for ABTS + and DPPH free radicals. Furthermore, the effect of SSCPs on carbon tetrachloride (CCl4 )‐induced liver injury was investigated in the mice. When compared with H‐SSCP and S‐SSCP, A‐SSCP significantly decreased the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), malondialdehyde (MDA), and reactive oxygen (ROS) to normal ( p  < .05) and increased the level of glutathione (GSH) to normal ( p  < .05). A‐SSCP was the most effective polysaccharide, yielding an approximately normal hepatic appearance with well‐preserved cytoplasm, obvious cell boundaries, with legible nuclei and nucleoli. This study indicates that polysaccharides extracted from soybean hulls via microwave‐assisted ammonium oxalate extraction have the potential to be developed as a new functional food contributing to the alleviation of liver damage. Abstract : The polysaccharides extracted from soybean hulls via microwave‐assisted ammonium oxalate extraction have the potential to be developed as a new functional food contributing to the alleviation of liver damage.